In Silico Evaluation of Chitosan's Antibacterial Potential Against Gram-Positive and Gram-Negative Bacteria - Maulidya, Selvira; Rahayu, Susi; Permatasari, Lina; Putri, Hudaynu Patya; Juniarza, A'yuni Guban (Jurnal Ilmiah Farmako Bahari, 2026)
Chitosan, a natural biopolymer, has attracted attention for its potential antibacterial properties against a wide range of pathogens. The escalating crisis of antibiotic resistance necessitates the exploration of novel antibacterial agents effective against both Gram-positive and Gram-negative bacteria. This study aimed to predict the antibacterial potential of chitosan against Staphylococcus aureus (a Gram-positive bacterium) and Escherichia coli (a Gram-negative bacterium) using a comprehensive in silico approach. Short chitosan oligomers, specifically trimers, were used to ensure computational feasibility and reliable molecular docking, as full-length polymers are too large for standard docking algorithms. Molecular docking simulations were performed using AutoDock to investigate the interactions between 13 chitosan compounds and the essential bacterial protein DNA gyrase, a key enzyme involved in DNA replication and repair. Binding affinities, interaction patterns (such as hydrogen bonding and hydrophobic contacts), and conformational changes were analyzed. The ligand showing the most favorable docking profile was further evaluated via molecular dynamics simulations using OpenMMDL to assess the stability of the complex over time. The results indicated that the chitosan derivatives, namely aminoethyl chitosan and dimethylaminoethyl chitosan, interact favorably with DNA gyrase in S. aureus and E. coli, respectively, with differential binding energies and interaction modes suggesting potential variations in inhibitory mechanisms between Gram-positive and Gram-negative bacteria. These computational findings support the potential of chitosan as a broad-spectrum antibacterial agent and provide a theoretical framework to guide further in vitro and in vivo validation of chitosan as a novel antibacterial compound.